Brazil: Basic elements to understanding the South American super power - Andrade A., Pablo (2010)
The essay focuses its attention in Brazil’s industrial policy. The author argues that it is that policy which helps explain both the new role of Brazil in the international economy, and this country’s projection of its power in South America. The analysis is made of two parts. In the first part, the author offers a study of Brazil’s transnational company, EMBRAER. The author claims that this company is a prime example of the success of long-term industrial policies. In the second part, the author shows the causal relations between Brazil’s foreign agenda towards South America, and the country’s pattern of industrialization. The essay concludes by extracting lessons for Ecuador’s foreign policy towards Brazil.